Choice of Law, Forum and Procedure in Conflict of Laws in Transnational and Cross-Border Commercial Disputes: Are Kenyan Judicial Decisions Veering Off to the Sidewalk? - Nyamweya, Gilbert (Journal of Malaysian and Comparative Law, 2008)
This article attempts to unravel the mystery surrounding the interpretation of choice-of-law, choice-of-forum and choice-of-procedure clauses in international trade. Most international contracts contain these clauses. The occurrence of disputes in these contracts is inevitable owing to the exigencies that pervade the environment in which they are performed. It is upon the backdrop of this stark reality that such contracts invariably incorporate dispute resolution mechanisms which take the shape of jurisdiction, choice-of-law, and procedural clauses. How courts interpret these clauses determines how parties define their affairs within the text of their contracts. The determination by courts as to which law or procedure is to apply or which country’s courts have jurisdiction often makes a significant difference in the determination of the substantive rights and obligations of the parties. The analysis of the approach and rhythm of courts around the world in the rigours of the application and interpretation of these clauses is, therefore, the propelling force behind this article. The analysis of Kenya’s judicial decisions have, in the hope of bringing to the fore Kenyan courts’ approach in the arena of private international contract law, have been considered along with judicial decisions from other jurisdictions.